Posisi Strategis Mata Kuliah Agama Islam pada Perguruan Tinggi Umum di Kota Palopo - Muhaemin Muhaemin (Edukasia Islamika, 2017)
This current study aims to explore and analyze the teaching and learning process of Islamic education at higher education institutions of non-Islamic studies, particularly Sekolah Tinggi Sosial Politik (STISIP) Veteran Palopo. It was qualitative research by employing a case study at STSIP Veteran Palopo. The data were collected through observation, in-depth interview, and documentation. The data were analyzed and concluded by regarding the focus of this study. The research findings reveal that firstly, the course content of Islamic Education at STISIP Veteran Palopo comprised three main aspects of Islamic teachings, namely: aqeedah (creed), sharia, and akhlaq (character) that were provided with several material development. Secondly, the lecturers delivered the learning materials by combining methods of lecturing, discussion, and recitations. Thirdly, the evaluation of teaching and learning process was carried out by having a written test. This study emphasizes the importance of revitalizing the presence of the Islamic Education course at higher education institutions of non-Islamic studies in terms of the learning materials, methods, and techniques of evaluation.